2014
DOI: 10.1016/j.mmcr.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

First imported coccidioidomycosis in Turkey: A potential health risk for laboratory workers outside endemic areas

Abstract: Coccidioidomycosis caused by Coccidioides immitis or Coccidioides posadasii is endemic in arid climate zones in America, travel-related cases have been reported. We report the first documented case of coccidioidomycosis in Turkey, overviewing reported cases in Europe and underlying difficulties of differential diagnosis outside endemic regions. The patient was an otherwise healthy 41-year-old man who travelled endemic areas. Laboratory diagnosis was based on direct microscopy of two subsequent subcutaneous bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The adverse events (AEs) related to the study medication also included mild dizziness, headache, eye discomfort and fatigue, and occurred along with significantly increased platelet counts above the normal range. Similar findings of headache and dizziness were also reported in previous studies of romiplostim [12][13][14][15] and eltrombopag [13][14][15][16][17][18]. In the eltrombopag study [13][14][15][16][17][18], a 2-4% elevation of aminotransferase was found; individual individuals had an interruption of treatment due to liver toxicity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The adverse events (AEs) related to the study medication also included mild dizziness, headache, eye discomfort and fatigue, and occurred along with significantly increased platelet counts above the normal range. Similar findings of headache and dizziness were also reported in previous studies of romiplostim [12][13][14][15] and eltrombopag [13][14][15][16][17][18]. In the eltrombopag study [13][14][15][16][17][18], a 2-4% elevation of aminotransferase was found; individual individuals had an interruption of treatment due to liver toxicity.…”
Section: Discussionsupporting
confidence: 87%
“…Each dose was investigated in a group of six individuals (five on hetrombopag and one on placebo). Plasma samples for PK analysis were collected before dosing and at 1,2,4,6,8,10,12,16,24,48,72,96 and 120 hr after hetrombopag administration.…”
Section: Study Amentioning
confidence: 99%
“…after inhalation of airborne arthroconidia (219). Recently, an imported coccidioidomycosis case has been detected in a 41-year-old other-wise healthy Turkish man who visited Texas area in the USA and returned to Turkey (220).…”
Section: Blastomycosis Is a Zoonotic Fungal Infection Caused Bymentioning
confidence: 99%